2021
DOI: 10.1088/1742-6596/1752/1/012021
|View full text |Cite
|
Sign up to set email alerts
|

Naïve Bayes Classifier and Particle Swarm Optimization Feature Selection Method for Classifying Intrusion Detection System Dataset

Abstract: The security of a network might be threatened by an intrusion aim to steal classified data or to find weaknesses on the network. In general, network main security systems use a firewall to control and monitor both incoming and outgoing network traffic. Intrusion Detection System can be used to strengthen network security. Several data mining methods have been used to solve Intrusion Detection System (IDS) problem on a network. On this paper we will use Naïve Bayes Classifier along with Particle Swarm Optimizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…It was tested with comparison to other CNN-based methods, and the outcomes showed that the application of PSO has a significant impact on the performance of the CNN. The PSO was also adopted in other IDS systems, such as [ 35 , 36 , 37 , 38 ].…”
Section: Related Workmentioning
confidence: 99%
“…It was tested with comparison to other CNN-based methods, and the outcomes showed that the application of PSO has a significant impact on the performance of the CNN. The PSO was also adopted in other IDS systems, such as [ 35 , 36 , 37 , 38 ].…”
Section: Related Workmentioning
confidence: 99%
“…The processing of subsets results in feature optimization, the optimized features are applied over the random forest algorithm in the form of different sized feature sets, such as 15, 20, and 35, and found that the random forest results into a better classification performance. An IDS for advanced metering infrastructure (AMI) in grid systems has been done by [7], as they are the target due to its two-way communication ability over internetwork. To overcome the problem of considering global and temporal characteristics of malicious information, the long short-term memory (LSTM) networks, based on the convolution neural network (CNN) algorithm, is used, which is fused with cross layer features over AMI IDS.…”
Section: Related Workmentioning
confidence: 99%
“…e intrusion detection system can monitor the traffic on the network and the log data stored in the computer and judge whether there is a malicious attack through analyzing various characteristics of the data [16]. e main components of the proposed intrusion detection system are hardware and software.…”
Section: Intrusion Detection Technologymentioning
confidence: 99%